Acute kidney injury following hepatectomy for hepatocellular carcinoma: incidence, risk factors and prognostic value. Issue 6 (June 2016) - Lim, Chetana; Audureau, Etienne; Salloum, Chady; Levesque, Eric; Lahat, Eylon; Merle, Jean Claude; Compagnon, Philippe; Dhonneur, Gilles; Feray, Cyrille; Azoulay, Daniel
Abstract: Background: Acute kidney injury (AKI) following hepatectomy remains understudied in terms of diagnosis, severity, recovery and prognostic value. The aim of this study was to assess the risk factors and prognostic value of AKI on short- and long-term outcomes following hepatectomy for hepatocellular carcinoma (HCC). Method: This is a retrospective analysis of a single-center cohort of 457 consecutive patients who underwent hepatectomy for HCC. The KDIGO criteria were used for AKI diagnosis. The incidence, risk factors, and prognostic value of AKI were investigated. Results: AKI occurred in 67 patients (15%). The mortality and major morbidity rates were significantly higher in patients with AKI (37% and 69%) than in those without (6% and 22%; p < 0.001). Renal recovery was complete in 35 (52%), partial in 25 (37%), and absent in 7 (11%) patients. Advanced age, an increased MELD score, major hepatectomy and prolonged duration of operation were identified as independent predictors of AKI. AKI was identified as the strongest independent predictor of postoperative mortality but did not impact survival. Conclusion: AKI is a common complication after hepatectomy for HCC. Although its development is associated with poor short-term outcomes, it does not appear to be predictive of impaired long-term survival.